Voltage-Gated Sodium Channel Blockers: Synthesis of Mexiletine Analogues and Homologues - Catalano, Alessia; Franchini, Carlo; Carocci, Alessia (Current Medicinal Chemistry, 2021)
Mexiletine is an antiarrhythmic drug belonging to IB class, acting as sodium channel blocker. Besides its well-known activity on arrhythmias, its usefulness in the treatment of myotonia, myotonic dystrophy and amyotrophic lateral sclerosis is now widely recognized. Nevertheless, it has been retired from the market in several countries because of its undesired effects. Thus, several papers were reported in the last years about analogues and homologues of mexiletine being endowed with a wider therapeutic ratio and a more selectivity of action. Some of them showed sodium channel blocking activity higher than the parent compound. It is noteworthy that mexiletine is used in therapy as a racemate even though a difference in the activities of the two enantiomers was widely demonstrated, with (–)-(R)-enantiomer being more active: this finding led several research groups to study mexiletine and its analogues and homologues in their optically active forms. This review summarizes the different synthetic routes used to obtain these compounds. They could represent an interesting starting point to new mexiletine-like compounds without common side effects related to the use of mexiletine.
Keywords: mexiletine analogues